Debt Relief as a Last Resort for the Lender of Last Resort? Monetary Financing – Doing It Right - Arne Hansen; Dirk Meyer (Intereconomics, 2021)
The coronavirus crisis has led to a sharp increase in the debt-to-GDP ratios of the euro area member states. Without external support, access to the capital market could be seriously threatened in the medium term for Italy, but also for other member states. While the Pandemic Emergency Purchase Programme, which is designed as a monetary policy instrument, is regarded by some as a violation of the prohibition of monetary financing, the Next Generation EU recovery fund is likely to direct the fundamental structures of the European Union towards a fiscal union with considerable redistribution elements. This article analyses an alternative strategy, namely debt relief by the European System of Central Banks through an EU debt agency. Such a scheme would be possible without amending the EU treaties and would avoid negative equity at the central banks. The question is under what circumstances would this approach be suitable and proportionate?
Keywords: 330; Wirtschaftskrise; Schuldenerlass; EU-Staaten